Pembuatan Batik Alam Berbahan Tumbuhan Sekitar Rumah - Misrita Misrita; Rosdiana Rosdiana; Srie Rosmilawati; Imam Qalyubi (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2020)
Batik is one of Indonesia's cultural arts, which has been integrated with Indonesian people since several centuries ago. However, so far, the batik produced still uses synthetic motifs and coloring, which can contribute to environmental pollution. Hence, people's interest in batik starts to diminish, so it is necessary to find breakthroughs in batik motifs and coloring, which are more environmentally friendly by using natural dyes. One of the natural dyes for batik is to use plant leaves that grow around the house, also called eco print, which is the activity of making leaves with specific patterns on a t-shirt, which produces motifs and colors obtained from the leaves. The target partners involved in community service activities are women's business groups in Palangka Raya, which are under the auspices of the Palangka Raya City Cooperative, Small and Medium Enterprises Agency, namely UKM Bawi Dayak Palangka Raya. This is because the batik produced so far still uses synthetic motifs and coloring. Assistance carried out for this group is to provide insight into knowledge and understanding of the importance of natural coloring and the danger of synthetic dyes. Build and encourage creativity informing design motifs and colors on fabric through the use of leaves that grow around the house. Outcome targets are t-shirt products that use leaves as motifs and natural dyes—introducing natural batik with the use of natural resources around.